School bullying in brazilian journals of school/educational psychology and educational psychology: an integrative review (Research, Society and Development, 2022)
The objective of this study was to investigate the presence and discussions about school bullying in Brazilian journals of school/educational psychology and educational psychology, classified in the Qualis indexing stratum – CAPES between A1 and B3. To this end, an integrative literature review was carried out with a time limit (2010 - 2021) on articles available in the digital collection of Brazilian journals identified in the aforementioned stratification and whose focus is on themes related to school/educational psychology or educational psychology. The works were selected based on the descriptors “bullying”, “school” and “school bullying”, in the fields: title, abstract and subject. In this process, productions written in a foreign language, with unavailable abstracts, were excluded and classified as essays, resulting in a total of 16 articles. In the end, it is emphasized that this review identified a low number of studies that address school bullying in the investigated journals, as well as stressing the need to expand the scientific production on bullying, in view of its importance for the basis of possible bullying prevention actions in the school context.